INTELLECTUAL PROPERTY AND ARTIFICIAL INTELLIGENCE: REGULATORY CHALLENGES AND SOLUTIONS - Eshchanova Dauletbike Ametbekovna; Mirzaliyev Ferdavsbek Dilmurod Ugli (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the impact of artificial intelligence (AI) on intellectual property, focusing on the challenges and opportunities it presents in the field of copyright. It explores the implications of AI-generated works, addressing issues of authorship and legal responsibility. Method: A comprehensive analysis was conducted, examining current applications of AI in creative industries, as well as reviewing international and national copyright legislation. Comparative insights were drawn to identify gaps and propose solutions for equitable copyright distribution between AI users and developers. Results: Findings indicate that the lack of a clear legislative framework for AI-generated works leads to significant disputes over authorship and ownership. National and international experiences highlight the urgent need for harmonized regulations to ensure fair and transparent copyright allocation. Novelty: This research contributes to the field by proposing a legislative definition of AI tailored to copyright contexts and offering actionable recommendations for addressing the ethical and legal complexities of AI-created content. These findings serve as a foundation for policymakers to adapt copyright laws in the era of AI.